دور مجلس المحاسبة في الوقاية من الفساد في الجزائر -  زغدي, فوزي; زوايد, راوية;  قادري, رمزي (University of Eloued جامعة الوادي, 2022)
تناولت دراستنا موضوع دور مجلس المحاسبة في الوقاية من الفساد في الجزائر، والذي بدوره يعد من أهم الهيئات الرقابية المعتمدة في الجزائر منذ نشأته في الوقاية ومكافحة الفساد الإداري والمالي، داخل المؤسسات العمومية المذكورة في المادتين 7 و8 من الأمر 95-20 المتعلق بمجلس المحاسبة. وتهدف هذه الدراسة إلى إيضاح الدور الذي يلعبه مجلس المحاسبة باعتباره آلية من الآليات المعتمدة في الوقاية من الفساد الإداري والمالي بالجزائر، وخاصة في مجال كشف وضبط المخالفات وجرائم الفساد المالي والإداري، من خلال ممارسته للصلاحيات المخولة له لأداء مهامه الرقابية، والمتمثلة في الرقابة الإدارية بنوعيها، رقابة نوعية التسيير وتقييم المشاريع والبرامج الحكومية، والرقابة القضائية المتمثلة في رقابة الانضباط في مجال تسيير الميزانية والمالية، والرقابة على حسابات الآمرين بالصرف والمحاسبين العموميين سواءً من حيث تقديمها أو مراجعتها، وإبراز العوائق المحيطة به والتي أثرت على نتائجه المحققة. وقد توصلت الدراسة إلى أن هذه الهيئة الرقابية رغم الدور الكبير الذي لعبته في الوقاية من الفساد بالجزائر، إلا أنها لم تحقق النتائج المرجوة منها، والسبب في ذلك قد يكون راجعاً للمشاكل الداخلية التي تتخبط فيها، والأوضاع المتدهورة وحالة التهميش التي تعيشها والضغوط الممارسة عليها من السلطة التنفيذية. ولكي تحقق هذه الهيئة الغاية التي أنشأت من أجلها، لا بد من منحها الاستقلالية الكاملة التي خولها إيَّها القانون، والعمل على إعادة النظر في بعض النصوص القانونية التي تحكمها، سواءً من حيث كيفية إنشاءها وتنظيمها وتسييرها والأحكام التي تصدرها. Our studies dealt with the issue of the role of the accounting consil in preventing from the corruption in turn is considered as one of the most important supervisory depacements approved in Algeria since its establishment in the prevention and fighting the administrative and financial corruption, inside the public institution which is mentioned in the Articles 7 and 8 of the order 95-20 that rolated to accounting counsil. This study aims to clarify the role of accounting counsil as a michanism of michanims approved in prevention from the administrative and financial corroption in Algeria, especially in the field of detacting and controlling violations and crimes of financial and administrative corruption by exercising the powers conferred upon him to perform his supervisory duties, the two types of administrative contrôle, management quality control and budget evoluation and government programs, judicial oversight represented in the control of discipline in the field of budget and financial management band oversight the accounts of those responssible for spending and public accountants whether in terms of their submission revwiew, and higblighting the obstacks surronding it that affected its achieved results . The study concluded that is this supervisory bodies, despite the big role which playedit in preventing from the corruption in Algeria did not achieve the desire results. This due to the enternal problems in which it is confused and the deteriorating conditions, the state of marginalization and the pressures escerted on them by them by the excutiv eauthority. In order for this body to acheive the purpose for which it was established, it must begranted the complete independence that the law has couferred upon it and wak to reconsider some of the legal tescts that govern it.
مذكرة ماستر